Estudo comparativo da variação da taxa de metabolismo utilizando o Fit bit e a calorimetria indireta em atletas e sedentários - Oliveira Filho, Antônio Fernandes de (2020)
Indirect calorimetry has been the reference method for assessing metabolic rate. The possibility of measuring basal metabolic rate and heart rate through wearable devices offers an opportunity for self-monitoring, real time data collection and data sharing for cardiovascular and sports medicine. The variety of devices commercialized has generated discussions about the validity of measurements obtained by devices with differentiated technology, which could undermine interpretation of results. Thus, the importance and necessity of this research is justified by studying and comparing variations of basal metabolic rate through indirect calorimetry and through wearable devices and bioimpedance. Objectives to compare the measurements of basal metabolic rate attained through distinct parameters of verification evaluating its realility . It is a cross-sectional observational study type control case. For the realization of this study the sample will be constituted by 60 male individuals in the age range of 18 to 40 years. The participants will be 30 professional football athletes and 30 sedentary individuals . The study will not include hypertensives, cardiopaths, diabetics, people with metabolic disorders and 3rd degree obesity, serious diseases or recente traumas. After obtaining the data the initial step is to carry out a descriptive analysis as to reach the statistical measure for the mean, median, and standard deviation, alongside their respective tables and graphs. After the descriptive analysis, tests of the variables will be carried out, namely: Kolmogorov-Smirvov test and the ShapiroWilk test, in order to know if the variables in the study follow the Normal distribution of probability. The following study will demonstrate statistically significant diferences between the measurements of Fit Bit instruments and indirect calorimetric. Of most relevance, the Fit Bit Instrument tends to indicate a lower TMB than the indirect calorimetry instrument. Anthropometry such as waist and neck perimeter will in fact be shown to correspond more closely with energy expenditure at rest. It is concluded therefore that caution is advisable for users of devices in relatoion to TMB readings. Data that would benefit health & fitness technology and ensure the possibility for interested researchers to incorporate the applications into multiple multimedia applications, optimizing activity- monitoring by the patient himself, and inducing positive behaviour change in personal healthcare and disease prevention.